Member Card and Social Media Promotion Strategies on Customer Loyalty - Salam, Karta Negara; Pratiwi Ar, Dhita; Rifai, Mesrawati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aimed to analyze the influence of the Member Card Promotion strategy and social media on Customer Loyalty at the Kaku Food Sudiang Branch in Makassar. A quantitative research design was employed, utilizing a survey method with a sample of 90 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to evaluate the structural relationships between the variables. The results revealed that while MCP had a significant positive effect on customer loyalty, the impact of SOM was statistically insignificant. The model demonstrated a moderate explanatory power, indicating that the combined strategy effectively explained a substantial portion of the variance in loyalty. These findings suggest that membership-based incentives are the primary drivers of customer retention in this context, whereas social media serves as a secondary engagement tool. The study highlights the need for Kaku Food to prioritize enhancing its membership program benefits while refining its social media content to bridge the gap between digital engagement and actual customer loyalty.